A cadaveric analysis of the blood supply to rectus Femoris. Issue 4 (April 2019) - Williams, M.; Caterson, J.; Cogswell, L.; Gibbons, C.L.M.H.; Cosker, T.
Summary: Background: Rectus femoris is a versatile muscle frequently used as a pedicled flap in reconstructive surgery. The anatomy and blood supply of rectus femoris needs to be clearly understood in order to safely preserve its reconstructive and functional capabilities. Classical anatomical description states that the proximal pedicle insertion into rectus femoris is 10– 15 cm from the anterior superior iliac spine (ASIS). The aim of this study was to dissect and identify the pedicular blood supply to rectus femoris and further map its morphology relative to the ASIS. Methods: A dissection of 20 embalmed thighs from 10 cadavers was conducted. The distance of arterial insertions into rectus femoris from the ASIS were recorded. The cohort was 60% male of median age 79 with statistical significance defined as p < 0.05. Results: 5%, 50%, and 45% of muscles demonstrated 1, 2, and 3 pedicles respectively. The mean distance from the ASIS to insertion of these pedicles was: proximal 13 cm (SD 2.6), middle 15 cm (SD 2.8), and distal 18 cm (SD 4.1). When grouped by number of pedicles, there was no difference in the mean height of proximal insertion. However, there was significant difference in mean intramuscular proximal-distal difference. These results were replicated when data were expressed as % of cadaver height. Conclusions: This study confirms the pedicular supply of rectus femoris but in contrast to classical literature demonstrates a greater range of pedicle insertions heights. We believe these observations should be considered when safely harvesting the pedicled rectus femoris flap.